2010
DOI: 10.5194/nhess-10-2475-2010
|View full text |Cite
|
Sign up to set email alerts
|

Incorporating the effects of topographic amplification in the analysis of earthquake-induced landslide hazards using logistic regression

Abstract: Abstract. Seismic-induced landslide hazards are studied using seismic shaking intensity based on the topographic amplification effect. The estimation of the topographic effect includes the theoretical topographic amplification factors and the corresponding amplified ground motion. Digital elevation models (DEM) with a 5-m grid space are used. The logistic regression model and the geographic information system (GIS) are used to perform the seismic landslide hazard analysis. The 99 Peaks area, located 3 km away … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…In available maps, these landslides have been merged into a few complex shaped polygons, blanketing the steep, gullied hills and covering 9.8 km 2 . However, a separate, local survey has found more than one thousand individual, shallow failures, many of which adjoined without making larger landslides (Lee et al, 2010). Together, these landslides had a total area of 7.22 km 2 , implying a significant area exaggeration by the automated mapping procedure.…”
Section: Landslide Mapping and Amalgamationmentioning
confidence: 99%
See 2 more Smart Citations
“…In available maps, these landslides have been merged into a few complex shaped polygons, blanketing the steep, gullied hills and covering 9.8 km 2 . However, a separate, local survey has found more than one thousand individual, shallow failures, many of which adjoined without making larger landslides (Lee et al, 2010). Together, these landslides had a total area of 7.22 km 2 , implying a significant area exaggeration by the automated mapping procedure.…”
Section: Landslide Mapping and Amalgamationmentioning
confidence: 99%
“…If the total area occupied by these six polygons is arbitrarily repartitioned into 1000 landslides of roughly equal size, set by the characteristic local ridge spacing and slope lengths of 100-150 m, then a 17fold reduction of the estimated landslide volume would result. This estimate could be refined with access to the local landslide data (Lee et al, 2010), which can be seen to have a non-uniform area-frequency distribution with hundreds of landslides with areas of 100 m 2 and one landslide of 0.1 km 2 .…”
Section: Landslide Mapping and Amalgamationmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study we examined the following environmental factors that are identified in the literature (Keefer 2000;Baeza and Corominas 2001;Duman et al 2006;García-Rodríguez et al 2008;García-Rodríguez and Malpica 2010;Hasegawa et al 2008;Lee et al 2008;Meunier et al 2008;Lee et al 2010) as possible landslide contributing factors: elevation (Digital Elevation Model, DEM), lithology, vegetation cover (represented by NDVI), land use, terrain roughness, relief degree of land surface (RDLS), profile curvature, and plan curvature. Lithology and land use are categorical variables, and the others are continuous variables.…”
Section: Environmental Factorsmentioning
confidence: 99%
“…In recent decades, important progress has been made by using regression analysis to investigate regional susceptibility. Correlation was established between factors representing topographic, geologic, and geographic features and earthquake-induced landslides (Keefer 2000;Baeza and Corominas 2001;Duman et al 2006;García-Rodríguez et al 2008, García-Rodríguez andMalpica 2010;Hasegawa et al 2008;Lee et al 2008;Meunier et al 2008;Lee et al 2010). The hazard analysis of Wenchuan earthquake-induced landslides conducted by Huang and Li (2008) and Qi et al (2009) also summarized the relationship between the distribution of landslides and factors such as lithology, local topography, and geomorphology based on post-disaster field investigations and the interpretation of remote sensing data.…”
Section: Introductionmentioning
confidence: 99%